Laying foundations for a “Right to Improve” - Lebloch, Kaspar; Rafetseder, Albert (Frontiers in the Internet of Things, 2024)
In this work, we introduce the vision of a “Right to Improve”: a hypothetical future law which should entitle consumers to modify and extend Internet of Things devices during the productive lifetime. Current European Union legislation as well as voluntary manufacturer interoperability initiatives fail to address user desires for adaptability, augmentability, and open-ended repurpoposing of Internet of Things (IoT) devices. We therefore argue in this paper for a Right to Improve that aims to fill the gaps left by today’s laws, conforms to consumer demands, and is powerful enough (by its statutory nature) to cause actual change. Our contribution is twofold. First, we summarize the relevant legislation (Ecodesign Directive, Sale of Goods Directive, and Right to Repair). We review the academic literature, and highlight technical and motivational factors that support a Right to Improve. Second, we suggest and discuss a number of open problems in need of consideration by academics, practitioners, companies, governing bodies, and the general public. A future formulation of the Right to Improve should take into account and balance the various contrasting views for efficacy on different levels, e.g., environmental benefit vs. economic risk. Change enabled by a Right to Improve may greatly enhance the usefulness of devices during their use phase, empowers consumers to create and compose devices and services to their own taste and requirements, makes devices more economically and ecologically sustainable by extending their useful lifetime, and creates new business opportunities.